Effects of Xenon on Neuroinflammatory Markers: a Prospective Pilot Study - A. I. Shpichko; R. A. Cherpakov; A. K. Shabanov; A. K. Evseev; I. V. Goroncharovskaya; O. A. Grebenchikov (Неотложная медицинская помощь)
The leading role of neuroinflammation as the culprit of a long-term impairment of consciousness in patients after injuries to the central nervous system forces us to look for new effective strategies for resolving this pathological process. Xenon reducing the intensity of the inflammatory response due to the impact on several links is potentially able to have a beneficial effect on this category of patients. Using laboratory equipment, we evaluated the effect of half-hour daily inhalations of a 30% air mixture with 30% xenon for 7 days on the level of markers of neuronal damage and regeneration of nervous tissue.AIM To study the effect of inhalation of an air-xenon mixture on the dynamics of markers of neuroinflammation and restoration of nervous tissue in patients after traumatic brain injury (TBI).MATERIAL AND METHODS We conducted a prospective randomized clinical trial evaluating the effect of inhaled xenon for sedation on the level of consciousness and spasticity in patients with prolonged post-coma impairment of consciousness. Patients were randomized into 2 equal groups. In Group I (Comparison, n=15) in addition to the standard treatment for TBI, each patient included in the study underwent 7 sessions of inhalation of an air mixture with an oxygen content of at least 30 vol.% for 30 minutes. In Group II (Xenon, n=15) in addition to the standard treatment, each patient included in the study underwent a half-hour inhalation with an air-xenon gas mixture (with a xenon content of 30 vol.% and oxygen — 30 vol.%) for 7 days, 1 time per day. The levels of interleukin-6, α-1 acid glycoprotein (AGP), S100 b protein and brain-derived neurotrophic factor were assessed before the first treatment and then once a day for 6 days.RESULTS The final evaluation included 12 patients from the Comparison Group and 12 patients from the Xenon Group. The greatest difference in the concentration of interleukin-6 between the Comparison and Xenon Groups was noted on the 5th day - 12.31 (10.21; 15.43) pg/ml vs. 7.93 (3.61; 9.27) pg/ml, respectively; however, the findings only tended to be statistically significant (p=0.07). When assessing the AGP level, the maximum difference was noted on the 4th day. In the Comparison Group, the AGP level was 0.81 (0.74; 0.92) pg/ml versus 0.614 (0.4; 0.79) pg/ml in the Xenon Group. And again, the data showed only a trend towards statistical significance (p=0.09). The highest level of brain-derived neurotrophic factor in the Xenon Group was observed on the 3th day — 0.1271 (0.046; 0.2695) pg/ml, which was statistically significantly higher than the one in the Comparison Group — 0.062 (0.036; 0.121) pg/ml (p=0.04). The concentration of S100 b protein during the entire observation period in both groups did not exceed 0.005 pg/ml.CONCLUSION Xenon inhalation according to the method proposed by the authors had a beneficial effect on the processes of neural tissue regeneration, however, with regard to neuroinflammation, its effects were not so pronounced.